Modification of Nanoclinoptilolite Zeolite with Hexadecyltrimethylammonium Surfactant as an Active Ingredient of Chromate-Selective Membrane Electrode - Alireza Nezamzadeh-Ejhieh; Gholamhosein Raja (Journal of Chemistry)
A novel chromate selective PVC membrane electrode was constructed using a hexadecyltrimethylammonium-surfactant modified zeolite (SMZ). Nano particles of an Iranian clinoptilolite zeolite were prepared by a ball-mill mechanical method and characterized by FT-IR, SEM and XRD. Best performance was exhibited at the membrane composition of SMZ : PVC : dioctyl phthalate (DOP) in the ratio of 4 : 32 : 64. This membrane worked well over a wide concentration range from to  mol L−1 of with a Nernstian slope of  mv per decade of concentration with detection limit of  mol L−1 in a wide pH range of 6.8–10.7. The response time of the sensor is 5–10 s over a period of 2 months with good reproducibility. The selectivity coefficients of the proposed electrode towards various interfering ions were determined by FIM and SSM methods. The sensor was successfully used as indicator electrode in the potentiometric titration of against Pb(II) and determination of chromium in an electroplating wastewater sample.